Assessing climate impacts of agroforestry system in LCA: case study in Zambia - Lahtinen, Oskari J. J.; Kyttä, Venla V.; Tuomisto, Hanna L. (Springer Nature, 2025)
Purpose: Agroforestry systems have the potential to reduce the carbon footprint (CF) of food production. One of the advantages of these systems is carbon removal from the atmosphere to biogenic carbon of trees. Nevertheless, there is not a common agreement on the method to include the climatic benefits of agroforestry systems in life cycle assessment (LCA). This study aims to evaluate methods for including biogenic carbon in the LCA of agroforestry systems. Methods: We studied three different maize production systems in Zambia: Low-input, High-input, and Agroforestry scenario. In the Agroforestry scenario, we studied a maize–Faidherbia albida system by investigating three methodological approaches with a functional unit (FU) of 1 ha. In Methodological Approach 1, biogenic carbon in the above- and below-ground biomass of trees in the agroforestry system was considered as a temporary carbon dioxide (CO2) storage via correction flow. In Methodological Approach 2, the biomass of trees was used as an energy source. In Methodological Approach 3, the mass balance principle was employed. The system expansion method was utilized to make each production system comparable. Three sensitivity analyses with a FU of 1000 kg of dry matter maize grain were also conducted following the methodological approaches. Results and discussion: The Agroforestry scenario had the lowest CF in all methodological approaches and in all sensitivity analyses when the maize grain yield level was the same as reported in the literature. Yet, uncertainty levels were high, as an IPCC tier 1 method was used. It was found that the biogenic carbon of the trees in agroforestry systems can be included in LCA by the currently available methods. The mass balance principle was a practical method for including the biogenic carbon of the trees in LCA. System expansion was another feasible method, wherein processes are added to the compared systems until they include the provision of the same functions. Conclusions: Biogenic carbon in the biomass of trees in agroforestry systems can greatly contribute to decreasing the CF if it is considered in LCA. If the FU and allocation methods are selected accordingly, the biogenic carbon can be effectively included in LCA. Based on the results of this case study, the maize–F. albida agroforestry system has the potential for decreasing the CF of maize production in Zambia.
Keywords: agroforestry; LCA; biogenic carbon; Zambia; system expansion; temporary storage; mass balance principle